In primary total hip arthroplasty, the direct anterior approach leads to higher levels of creatine kinase and lower levels of C-reactive protein compared to the posterolateral approach: a propensity score matching analysis of short-term follow-up data - Luca De Berardinis; Marco Senarighi; Luca Farinelli; Fjorela Qordja; Alberto Gallo; Marco Spezia; Antonio Pompilio Gigante (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background This retrospective study compares the invasiveness of the direct anterior approach (DAA) and the posterolateral approach (PLA) in total hip arthroplasty (THA) by assessing three widely used inflammation-related serum markers in the first ten post-operative days. Methods The database of our institution was mined for primary THAs conducted by the DAA or the PLA from February 2020 to June 2022. Demographics and creatine kinase (CK), C-reactive protein (CRP), and white blood cells were compared. Propensity Score Matching (PSM) analysis (1:1 ratio) was conducted based on multiple variables. Results PSM analysis yielded 44 pairs of DAA and PLA patients. CK was significantly higher (p < 0.001) in the DAA than in the PLA group on postoperative day (POD) 2, 5 and 10. The POD2, POD5 and POD10 CK/preoperative CK ratio was 12.9, 5.0 and 0.8 in DAA and 8.8, 3.3 and 0.6 in PLA (p = 0.017, p = 0.012 and p = 0.025, respectively). The POD2, POD5 and POD10 CRP/preoperative CRP ratio was 95.1, 65.6 and 22.8 in PLA and 34.7, 23.3 and 8.9 in DAA (p < 0.001, p = 0.002 and p < 0.001, respectively). Conclusion PSM analysis of early postoperative CK and CRP values demonstrated that the DAA should be considered as a less stressful approach, not as a muscle-sparing or a minimally invasive THA approach.